Esoteric Buddhism in China: engaging Japanese and Tibetan traditions, 1912-1949 - Wu, Wei (The Sheng Yen series in Chinese Buddhist studies, 2024)
"After the fall of the Qing dynasty in early twentieth-century China, Buddhists lost imperial patronage and faced both a declining monastic economy and challenges from antireligious campaigns. In order to rejuvenate Buddhism in China, some Buddhists looked to non-Chinese esoteric traditions, leading to the introduction of a rich array of ideas and practices that had a lasting impact on Chinese Buddhism In Esoteric Buddhism in China, 1912-1949, Wei Wu explores the ways that Chinese Buddhists engaged with esoteric Buddhist ideas and practices in the first half of the twentieth century, and examines the effects of this reintroduction in Chinese society. She argues that a process of translating and interpreting esoteric Buddhism in the Chinese cultural context was developed and that a plurality of meanings about esoteric Buddhist rituals, customs, doctrines, and practices was generated in this process. By examining the doctrinal, ritual, and institutional ways that these interpretations were operated and circulated, Wu reveals how significantly esoteric Buddhism shaped the religious landscape in modern China"--